2001
DOI: 10.1021/la0109516
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of a Sugar-Based Gelator in Water:  Its Remarkable Diversity in Gelation Ability and Aggregate Structure

Abstract: A new sugar-based gelator 1 was synthesized, and its gelation ability was evaluated in organic solvents and water. Very surprisingly, 1 was found to gelate organic solvents as well as water, indicating that 1 can act as an amphiphilic gelator. We characterized on superstructures of an aqueous gel from 1 using SEM, TEM, NMR, IR, and XRD. The aqueous gel 1 formed a three-dimensional network with 20-500 nm diameter puckered fibrils. In addition, the chiral aggregate was found to be largely twisted helical ribbons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
186
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(191 citation statements)
references
References 35 publications
4
186
0
1
Order By: Relevance
“…The d-spacing of the aggregates were approximately 4.1, 2.06, 1.38, 1.05 nm and corresponded to the twice of the extended molecular length of GDA a Present address: Department of Nano-Fusion Technology Thermolon Korea, Co. Ltd, Jung-gu, Busan (2.05 nm, by the Chemdraw 3D molecular modeling) that is quite similar to the length of two molecules of GDA surfactant. 25 These results indicated that a gelation material maintained a bilayered structure with a 4.1 nm of bimolecular sheet which was corresponded to the (100) plane ( Figure S1A). The SEM image strongly supported the lamellar structure, which could be explained due to the hydrogen bonded bilayered assembly of GDA dimeric amphiphile ( Figure 1A).…”
mentioning
confidence: 70%
“…The d-spacing of the aggregates were approximately 4.1, 2.06, 1.38, 1.05 nm and corresponded to the twice of the extended molecular length of GDA a Present address: Department of Nano-Fusion Technology Thermolon Korea, Co. Ltd, Jung-gu, Busan (2.05 nm, by the Chemdraw 3D molecular modeling) that is quite similar to the length of two molecules of GDA surfactant. 25 These results indicated that a gelation material maintained a bilayered structure with a 4.1 nm of bimolecular sheet which was corresponded to the (100) plane ( Figure S1A). The SEM image strongly supported the lamellar structure, which could be explained due to the hydrogen bonded bilayered assembly of GDA dimeric amphiphile ( Figure 1A).…”
mentioning
confidence: 70%
“…A related compound containing an amide linkage between the hydrocarbon and acyl chain (18) was found to form a three-dimensional network of 20-500-nm-diameter puckered fibrils. 60 …”
Section: Glycolipidsmentioning
confidence: 97%
“…A rigid network structure forms due to a self-organization of gelator molecules by various physical interactions: van der Waals, hydrogen bonds, p-bonds, etc. [10]. However, in such system no irreversible (chemical bounds) interactions between the solvent and the gelating material occur; hence, the separation of the liquid phase and the rigid gel formed becomes possible, opposite than in the case of chemical gels.…”
Section: Introductionmentioning
confidence: 99%